2019
DOI: 10.1111/mcn.12817
|View full text |Cite
|
Sign up to set email alerts
|

Linear growth faltering and the role of weight attainment: Prospective analysis of young children recovering from severe wasting in Niger

Abstract: Efforts to reduce the impact of stunting have been largely independent of interventions to reduce the impact of wasting, despite the observation that the conditions can coexist in the same child and increase risk of death. To optimize the management of malnourished children—who can be wasted, stunted, or both—the relationship between stunting and wasting should be elaborated. We aimed to describe the relationship between concurrent weight and height gain during and after rehabilitation from severe wasting. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 39 publications
(45 reference statements)
3
40
1
Order By: Relevance
“…29,30 Individual studies have suggested that early wasting could predispose children to later linear growth failure. 4346 We hypothesized that early wasting could contribute to subsequent linear growth restriction, and early growth failure could be consequential for persistent growth failure and mortality during the first 24 months of life. Among cohorts with monthly measurements, we examined age-stratified linear growth velocity by quartiles of WLZ at previous ages.…”
Section: Consequences Of Early Growth Failurementioning
confidence: 99%
“…29,30 Individual studies have suggested that early wasting could predispose children to later linear growth failure. 4346 We hypothesized that early wasting could contribute to subsequent linear growth restriction, and early growth failure could be consequential for persistent growth failure and mortality during the first 24 months of life. Among cohorts with monthly measurements, we examined age-stratified linear growth velocity by quartiles of WLZ at previous ages.…”
Section: Consequences Of Early Growth Failurementioning
confidence: 99%
“…Both conditions should be targeted specifically, although programmatically interventions can be combined to maximize the impact. Indeed, although limited, there is evidence that stunted and wasted children respond well to treatment of wasting and that recovery from wasting may be followed by linear growth acceleration [12,48].…”
Section: The Concurrence Of Wasting and Stuntingmentioning
confidence: 99%
“…2,13,14 Wasting may also be a risk factor for stunting. 8,15,16 Research and programs often consider wasting and stunting separately, but similar risk factors underlie each condition, 17,1819 wasting may reduce linear growth, 20 and concurrent wasting and stunting heightens mortality risk far beyond the mortality risk of either condition in isolation. 3,7,8,21 The failure to implement large scale programs to prevent wasting may reflect a historic focus of programs and research on the treatment of severe wasting rather than prevention, or an incomplete understanding of the optimal time to intervene.…”
Section: Introductionmentioning
confidence: 99%